Death of Bacillus subtilis Auxotrophs Due to Deprivation of Thymine, Tryptophan, or Uracil - Pritikin, William B. (1966)
Pritikin, William B. (University of California, Los Angeles), and W. R. Romig. Death of Bacillus subtilis auxotrophs due to deprivation of thymine, tryptophan, or uracil, J. Bacteriol. 92:291–296. 1966.—Auxotrophic mutants of Bacillus subtilis 168 that require either tryptophan, uracil, or thymine died rapidly when deprived of any of these compounds. Phage PBS1 was produced by infected B. subtilis 168 (thy try-2) deprived of thymine. Phage PBS1 was not produced by infected B. subtilis 168 (try-2) deprived of tryptophan or infected B. subtilis 168-15 (try-2 ura) deprived of uracil. B. subtilis 168 thy try-2 and 168-15 could be transduced by phage PBS1 after prolonged deprivation of tryptophan or uracil, respectively. When B. subtilis 168-15 was transduced to uracil independence by phage PBS1, the uracil-independent transductants became immune to uracil-less death within 10 min of exposure to phage, and began to multiply within 2 hr after exposure to phage at an incubation temperature of 46 C.